IMPLEMENTATION OF RISK MANAGEMENT OF THE MUDARABAH CONTRACT AT BMT UGT NUSANTARA BONDOWOSO KOTA BRANCH - Sofiatul wahidah (Universitas Nurul Jadid, 2024)
This study aims to explain the implementation of risk management in the mudarabah contract at BMT UGT Nusantara Bondowoso Kota Branch, especially in financing the agricultural sector. Qualitative methods are used to collect data through interviews, observations, and documentation studies. The results of the study show that the financing risks at BMT include payment congestion due to crop failures and customer dishonesty in reporting business results. The risk management implemented involves risk identification using the 5C principle (Character, Capacity, Capital, Collateral, Condition), risk measurement based on collectibility categories, risk monitoring through direct supervision and evaluation of customer finances, as well as risk control through warning letters and collateral confiscation. Although risk management at BMT UGT Nusantara Bondowoso Kota Branch is quite good, there are still shortcomings in socialization to customers about the importance of risk management. Increased accuracy in analyzing financing and training to customers is expected to minimize the risk of problematic financing for mudarabah.